Entrepreneurship Education in Nigeria Tertiary Institutions and its Impact on Students’ Entrepreneurial Career Intentions. A Study of Students at Federal Polytechnic Ekowe - Fems, Kurotimi Maurice (Open Science Journal, 2020)
Purpose: Entrepreneurship education as an influencer of graduate entrepreneurial intention is gaining massive attention amongst practitioners, policy makers and academics across the globe. The proliferation of entrepreneurship courses in universities around the world is evident of this wide acceptance of entrepreneurship education as a strategy for graduate entrepreneurship. The purpose of this research paper is to ascertain the impact entrepreneurship education has on students’ entrepreneurial career intentions. Methodology: The article includes a review of literature in entrepreneurship education and entrepreneurial intention to gain background knowledge. This research is a qualitative, interpretive phenomenological study and relies on narrative as a means of knowing, and as a form of communication. The scope of the study is year one students at the Federal Polytechnic of Oil & Gas Ekowe in the departments of Computer Science, Science Laboratory Technology and Statistics. The questionnaire was designed in a semi-structured way and distributed to students to return after 7 days to allow for proper articulation of narratives. Findings: A total of 42 students participated in the interview and 42 returned. 28.57% representing 12 students showed intention to start a business, 40.48% (17 students) desire to get a job after graduation while 13 students (30.95%) are unsure what they want to do after graduation. The results indicate that entrepreneurship education has a positive impact on students’ entrepreneurial career intention but other than EE, it was also revealed from participants’ narratives that age, prior experience and parents’ status have positive influence on graduate entrepreneurial decisions. Implication of Findings: Findings will aid curriculum designers and educational policy makers to scrutinize and re-examine EE programmes and how they are taught to enhance practice. Originality: Narratives and storytelling methods are not the common methods adopted in entrepreneurship education and entrepreneurial intention research. More research should be carried out using this method to validate results from this approach.